Factors Associated With Alcohol Use Disorder Among People Living With HIV/AIDS Attending Art Clinic, Mizan Tep University Teaching Hospital, South West Ethiopia - Gebre BB (Dove Medical Press, 2019)
Bereket Beyene Gebre School of Nursing, College of Medicine and Health Science, Hawassa University, Hawassa, EthiopiaCorrespondence: Bereket Beyene GebreSchool of Nursing, College of Medicine and Health Science, Hawassa University, Hawassa, EthiopiaEmail bereket2007beyene@gmail.comIntroduction: Alcohol use is a major public health concern in global settings. It is very common among people living with HIV/AIDS, leading to physical and mental complications.Objective: To assess the magnitude of alcohol use and factors among HIV/AIDS positive adults visiting ART clinic at Mizan Tep University Teaching Hospital (MTUTH), Southern Ethiopia from October 2017 to December 2017.Methods: A facility based cross-sectional study was conducted with a sample of 332 HIV positive adults who came to ART clinic at MTUTH using systemic random sampling technique. Data were entered into EPidata 3.1 version and then analyzed by SPSS version 20. Binary logistic regressions have been used to identify the association between an independent variable with the dependent variable.Result: A total of 332 participants were enrolled in the study with the prevalence of alcohol use disorder (AUD) of 18.4%. Factors associated with alcohol use disorder were sex AOR=3.48 (95% CI: 1.27, 9.59), cigarette smoking AOR=5.12 (95% CI: 4.02, 8.61), “khat” chewing AOR=3.23 (95% CI: 2.06.6.89), and CD4 count of 0–200 AOR = 19.49 (95% CI: 1.74, 218.4).Conclusion: The prevalence of alcohol use disorder was high. It is independently associated with male patients, cigarette/tobacco smokers, khat chewers, and low CD4 count.Keywords: magnitude, alcohol use disorder, factors